The ‘internationalisation’, or ‘Englishisation’, of higher education in East Asia - Galloway, Nicola; Numajiri, Takuya; Rees, Nerys (Higher education, 2020)
In recent years, one of the most significant trends in higher education in non-anglophone countries has been the growth in English Medium Instruction (EMI). However, provision is rapidly outpacing empirical research. This study examined how macro-level education policy with regard to EMI is both implemented and conceptualised at the institutional and classroom level in Chinese and Japanese universities. Utilising questionnaires with home students (n = 579) and staff (n = 28), interviews with home students (n = 29) and staff (n = 28) and four focus groups with staff and four with home students, in addition to questionnaires (n = 123), interviews (n = 10) and three focus groups with international students, the study provides insights into how EMI policy is operationalised, including types of programmes and language use, and how it is conceptualised by different stakeholders. The results highlight contextual constraints to policy implementation, calling for the need for more research into this growing trend and curriculum evaluation to inform context-sensitive ways to implement EMI policy. It also calls for a critical examination of monolingual EMI policies and academic norms amidst growing multilingualism in the EMI classroom as well as clear goals and objectives due to varying conceptualisations of the purposes of EMI amongst staff and students.